Critical analysis of drug promotional literature available to the medical practitioners - Pai Kakode, Kalyani V.; Bhandare, Padma N. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: To ascertain whether the pharmaceutical companies are following the WHO criteria for “Ethical medicinal drug promotion 1988” and “OPPI Code of pharmaceutical marketing practices, 2012” and to what extent. Also, to evaluate the therapeutic claims made by them in their drug promotional literature and other aspects. Methods: Drug Promotional Literature (DPL) from different pharmaceutical companies was collected from various Medical practitioners and analysed to see if they achieved objectives. Therapeutic claims made by them were classified as authentic, exaggerated, controversial, false, and misinterpreted. Results: Total 250 DPLs were collected and critically analysed for information content. Out of the 11 WHO criteria for ethical medicinal drug promotion (1988), Majority (30%) followed only 54.54% of the criteria while only 4% followed 100% of the criteria. The total number of claims in the 250 DPL were 354 of which 52.8% were authentic and 47.2% were misleading. From the misleading claims: 28.7% were exaggerated, 34.7% were controversial, 22.8% were false, 23% were ambiguous. Conclusions: This study enabled us to find out to what extent the pharmaceutical industries follow the standard criteria for DPL and evaluate the claims made by them. DPL is one of the important sources of drug information. Some of the pharmaceutical companies failed to follow the WHO criteria while advertising their products in order to make them look more lucrative having an underlying commercial motive. As they influence prescribing patterns of the clinicians, misleading promotional literature would result in irrational prescribing of drugs. To avoid this, DPL has to be critically evaluated.